Educational multimedia software for English language vocabulary - Lauc, Tomislava (Array, 2006)
The paper describes research on using multimedia educational software for the English language vocabulary within the English language course lesson. The research was conducted by offering two forms of the same learning content. One form consisted of classical paper material, and the other one was in the form of the software. Research was conducted with two groups of learners attending an English course as a foreign language course, i.e. two groups of learners on the same level of English language knowledge. One group dealt with the classical paper material, and the other group dealt with the interactive multimedia software. The learners’ existent knowledge of the learning material was pretested at the beginning of both lessons, and both groups of learners got the same final test. The results indicated the great level of disparity between the two groups of learners regarding their acquisition of new vocabulary.